Der Kampf : sozialdemokratische Monatsschrift (Wien: Volksbuchhandlung)
"Redactie: Oskar Pollak, Otto Bauer, Max Werner, Gaetano Salvemini, Z. Topalowitch, Karl Renner, Helene Bauer, Otto Leichter, Otto Jenssen, W.D. Vliegen, Karl Kautsky, Jean Zyromski"